(untitled) (Research, Society and Development, 2020)
Introduction: Viral diseases affect the world population several times during their lives, and are considered a serious public health problem. Medicinal plants and functional foods have a beneficial influence on human and animal health, due to the bioactive compounds present in plants and foods, which are able to modulate the action of pathogens and reduce the risk of diseases. Although some medicinal plants have their widespread use in folk medicine as antivirals and / or immunostimulants, scientific information is needed to validate their benefits. Objective: To review in scientific journals and describe the antiviral effects and immunomodulatory properties of elderberry (Sambucus sp.), Garlic (Allium sativum) and Ginger (Zingiber officinale) species. Methodology: This review was developed from an exploratory review of articles selected on the Scielo, Google Scholar and PubMed database platforms. Results: The journals reviewed in this study showed that some species of the genus Sambucus, Allium sativum L. and Zingiber officinale R., have potential antivirals and immunostimulants, being able to reinforce protection against pathogens even against the Coronavirus. Final considerations: The plants evaluated in this study can be considered as an alternative in the treatment of viral infections and / or conditions that need to stimulate the immune system. It is emphasized, however, that more research must be carried out to further evaluate the spectrum of action and their respective dosages, in order to standardize their uses.